Color masking of developmental enamel defects: a case series - Torres, C. R. G. [UNESP]; Borges, A. B. [UNESP] (Operative Dentistry Inc, 2015)
Developmental defects involving color alteration of enamel frequently compromise the esthetic appearance of the tooth. The resin infiltration technique represents an alternative treatment for color masking of these lesions and uniformization of tooth color. This technique is considered relatively simple and microinvasive, since only a minimal portion of enamel is removed. This article illustrates the color-masking effect with resin infiltration of fluorosis and traumatic hypomineralization lesions with a case series. The final esthetic outcomes demonstrated the ability of the resin infiltrant to mask the color of white developmental defect lesions, resulting in satisfactory clinical esthetic improvements. However, in more severe cases, the color-masking effect was not complete.